Diabetic retinopathy: a tool for cardiovascular risk stratification - Angelo Avogaro; Gian Paolo Fadini (Сахарный диабет, 2019)
Randomized, cross-sectional, and prospective studies have demonstrated that microvascular complications in patients with diabetes are not only the cause of blindness, renal failure and non-traumatic amputations, but also powerful predictors of cardiovascular complications. The pathophysiology of diabetic microvascular complications is determined by several factors including epigenetic modifications, and reduced release of circulating progenitor cells by the bone marrow. Identifying microvascular complications, in particular retinopathy, increases the ability to stratify patients in terms of cardiovascular risk. There may no longer be a rational to consider microangiopathy and macroangiopathy as entirely separate entities, but they should most likely be viewed as a continuum of the widespread vascular damage determined by diabetes mellitus.